ANALISIS SEMIOTIKA IKLAN ROKOK U MILD VERSI TIAP LUKA PUNYA CERITA - Roy Sensia Ari Wibowo; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study entitled Analysis of Semiotics of Masculinity In U Mild Ciggarets Version “Tiap Luka Punya Cerita”. The Purpose of this advertisement is to knowing the denotation meaning, conotation meaning and myth that represented in this ad and to knowing the meaning of masculinity by five of masculinity reachness from Archer and Lloyd.This research using analysis of semiotic theory by Roland Barthes, there are meaning of signifier, signified, denotation level, conotation level. In this advertisement have fourteen seconds of duration that divided in five scenes. The mhetod that used in this research is cualitative mhetod. The researcher downloaded the video of this advertisement for the first step from youtube, then turning out the video being the pieces of pictures which all will be analyzed. The video made be eight pictures and divided in five scenes.The lifestyle of society nowadays so close with cigarrets. Not only adults, teenagers even the children are many in comsuming cigarrets. Image of cigarrets advertisement in televison fixed with the kind of closeness objection that advertised. Cigarret is a regular consumption for man. The man is always showed up in way of masculinity.This research is using a couple of relevant theorys, are : Advertisement, semiotic, Roland Barthes semiotic theory, visual communication semiotic, masculinity, film structure and sounds. Denotation meaning of this ads is representing men that have masculinity by their looks. The men who can representing masculinity are they who have sharp body, hard and love the things of dangerousity and have the youth soul. The other things the men who can called masculine man if could handle broken hearted soul that caused by women. The conotation that showed up in this ads is represented by a friendship of man. Cigarrets conotated as a friend and the men who have youth soul..Keywords: Analysis, Semiotic, Cigarrets, Advertisement, Masculinity.